THE THE INFLUENCE OF STEAM, MEDIA-ASSISTED STEAM, AND CONVENTIONAL ON PRIMARY ISLAMIC EDUCATION OUTCOMES - Jefpi Milda; Fajri Ismail; Yulia Tri Samiha; Muhammad Isnaini; Syarnubi (Universitas Islam Negeri Mataram, 2026)
This research is motivated by low learning outcomes in Islamic Religious Education (PAI) for elementary school students, which are still dominated by conventional teaching and lack student-centered approaches. This study uses a quantitative approach with a quasi-experimental factorial 2 × 3 design and a non-equivalent posttest-only control group. The research population comprised all grade VI students at SD Negeri in Sukarami District, Palembang, and a purposive sample of 90 students was selected. The research instrument is a PAI learning outcome test that has been tested for validity, reliability, difficulty, and differentiation. The data analysis used a two-way ANOVA, followed by a post hoc test using the HSD Tukey test at a significance level of 0.05. The results showed that: (1) there were significant differences in PAI learning outcomes between students taught using STEAM, media-assisted STEAM, and conventional learning approaches; (2) the learning outcomes of students taught using the media-assisted STEAM approach are higher than STEAM without conventional media and learning; (3) there are differences in PAI learning outcomes based on gender, where female students have higher average learning outcomes than male students; and (4) there is a significant interaction between learning approaches and gender on students’ PAI learning outcomes. Overall, the media-assisted STEAM approach is most effective in improving PAI learning outcomes in both male and female students. differences in student characteristics based on gender.